2004
DOI: 10.1111/j.0022-202x.2004.23442.x
|View full text |Cite
|
Sign up to set email alerts
|

FOXN1 Is Critical for Onycholemmal Terminal Differentiation in Nude (Foxn1nu) Mice

Abstract: Nude mice have a mutation in the transcription factor Foxn1(nu), resulting in downregulation of hair keratins. Although hair follicles develop normally, the hair fibers become structurally weak, curl, and break off at the surface. Nails in nude mice are deformed, based on alterations of the onychocyte differentiation process. Elemental microanalysis of the nail plate reveals marked decreases in sulfur concentrations in the nude mouse nail plates. Immunohistochemistry shows a lack of keratin 1 expression in ter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
76
2

Year Published

2006
2006
2021
2021

Publication Types

Select...
3
3
1

Relationship

2
5

Authors

Journals

citations
Cited by 57 publications
(82 citation statements)
references
References 48 publications
4
76
2
Order By: Relevance
“…Alpha keratins are found in the feather sheath and barb ridges but are rapidly overwhelmed by deposition of beta keratins (Alibardi, 2013). Since one function of transcription factor FOXN1 in mice is the activation of alpha keratins 2-6 (Schlake et al, 2000;Mecklenburg et al, 2004) and birds appear primarily to use beta keratin proteins in feathers, it has not been tested whether feathers express FOXN1. We previously showed that another Forkhead transcription factor, FOXE1, is transcribed in the feather filament (Yaklichkin et al, 2011), and its mammalian ortholog is implicated in hair morphogenesis (Brancaccio et al, 2004).…”
Section: A Expression Of Chick Foxn1 In Feathers 59mentioning
confidence: 99%
See 2 more Smart Citations
“…Alpha keratins are found in the feather sheath and barb ridges but are rapidly overwhelmed by deposition of beta keratins (Alibardi, 2013). Since one function of transcription factor FOXN1 in mice is the activation of alpha keratins 2-6 (Schlake et al, 2000;Mecklenburg et al, 2004) and birds appear primarily to use beta keratin proteins in feathers, it has not been tested whether feathers express FOXN1. We previously showed that another Forkhead transcription factor, FOXE1, is transcribed in the feather filament (Yaklichkin et al, 2011), and its mammalian ortholog is implicated in hair morphogenesis (Brancaccio et al, 2004).…”
Section: A Expression Of Chick Foxn1 In Feathers 59mentioning
confidence: 99%
“…In addition to regulating keratins (e.g., Mecklenburg et al, 2004), the regulation of MHC Class II genes, BRD2 (Bromodomain-containing gene 2), CTSL (Cathepsin L, a lysosomal protease), CD40 (TNF-related receptor), and DLL4 (delta-like gene 4) was positively correlated with FOXN1 dosage (Nowell et al, 2011;hESnet). To determine if these components represent a gene regulatory network that is conserved in other FOXN1-expressing tissues, we used in situ hybridization to evaluate the expression of chick homologs of these genes in feathers and other epidermal appendages.…”
Section: Expression Of Foxn1 and Its Putative Target Genes In Cutaneomentioning
confidence: 99%
See 1 more Smart Citation
“…A concurrent qualitative or semi-quantitative follow up can be done, when the SEM is appropriately equipped to perform element analysis on the hair shafts. Sulfur levels are higher in hair shafts and nails than epidermis of the skin due to the presence of the hard (hair and nail) keratins and keratin associated proteins which are often proteins containing high to ultrahigh sulfur containing amino acids [102]. Hair defects are often due to low sulfur levels, e.g.…”
Section: 23mentioning
confidence: 99%
“…Samples should be examined for an average of at least 300 live seconds to ensure a comprehensive reading is obtained [102].…”
Section: 23mentioning
confidence: 99%